Student performance in large cohorts: Evidence from unexpected enrollment shocks - Friederike Hertweck (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
This article investigates the effects of large groups of first-year students on individual college performance. The study is based on administrative micro-level data from the universe of higher education institutions in Germany. The empirical strategy exploits shocks in undergraduate enrollment induced by policymakers' underestimation of expected demand for college. The results show that students in large cohorts of freshmen have a lower probability to complete their degree on-time, partly because students take longer to attain their college degree and partly because more students are forced to de-register. The results are relevant for policymakers to promote educational expansion without jeopardizing student performance. @Diese Studie untersucht die Auswirkungen großer Studienanfangskohorten auf den individuellen Studiumserfolg. Sie basiert auf administrativen Mikrodaten aller Hochschulen in Deutschland. Die Unterschätzung der erwarteten Nachfrage nach Studienplätzen durch die Kultusministerkonferenz wird hierbei als Immatrikulationsschock empirisch ausgenutzt. Die Ergebnisse zeigen, dass Studenten in großen Studienanfängerkohorten eine geringere Wahrscheinlichkeit haben, ihr Studium in der Regelstudienzeit abzuschließen, zum Einen, weil sie mehr Semester benötigen, ihren Hochschulabschluss zu erreichen, und zum Anderen, weil mehr Studierende ihr Studium "endgültig nicht bestanden" haben und so ohne Abschluss exmatrikuliert wurden. Die Ergebnisse sind für politische Entscheidungsträger von Bedeutung, um die Bildungsexpansion zu fördern, ohne den Erfolg der Studierenden zu gefährden.
Keywords: I20; I23; J08; 330; Higher education; cohort size; student performance; schooling reforms; policy evaluation